Acquisition of a talent pool: AK venture story - A. Jalil, Emy Ezura; Mohd Saifudin, Adam; Zainuddin, Nizamuddin; Bahaudin, Ahmad Yusni; Jamaludin, Roslan (2018)
Ninety percent of world trade has been delivered by maritime.The significant role played by maritime industry is undoubtedly crucial for the world economic growth and prosperity.Therefore, AK Ventures had been chosen to portrait the dynamics of maritime management and operations.Ak Ventures is unique because the company is only focus on Maritime but they also diversified in other sectors in economic such as education (AK Academy) tourism (AK Travel) and property management (AK Property).Due to the vast activities of AK Ventures they can still perform will in all sectors with the minimum human resources and also the span of management of AK Venture is not so called dynamic organization but rather a centralized management whereby the focus and the power of authority lies under one or two individual.From the case it can be observed that AK Venture doesn't have any proper strategic planning and human capital and retention plan.However, it can still perform with the full satisfied human resources (base on the interviews).This is very in contrary with the human resource management studies. The focus of this case is on human resources planning, retaining, training and development of AK Academy.Applications of those theories and strategies are paramount in understanding, analyzing, concluding and solving of the teaching notes.